THE EFFECT OF HEALTH EDUCATION WITH AUDIOVISUAL METHODS ON KNOWLEDGE FIRST AID FOR BURN ON HOUSEWIVESIN GENERAL POLY ROOM PKM PURI MOJOKERTO REGENCY - Binarti Dwi Wahyuningsih (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
ABTRACT Burns are a form of trauma that occurs as a result of human activities in the household, industry, or natural disasters. Lack of knowledge makes many people still believe that using toothpaste, ice, raw egg white, soy sauce can heal burns, after doing research on kitchen ingredients it will worsen burns because they will expand and not stop the spread of burns. The purpose of this study was to determine the effect of health education with audiovisual methods on knowledge of burn wound first aid among housewives in General Poly Room PKM Puri Mojokerto Regency. The population in this study were housewives in General Poly Room PKM Puri Mojokerto Regency. as many as 60 people. Sampling in this study using purposive sampling. The sample in this study were all housewives as many as 50 people. Before being given health education on first aid burns, the level of knowledge was less than 28 people (56%). After being given health education about first aid for burns using the audiovisual method, some of the respondents had good posttest scores with a total of 33 respondents (66%). Atatistic test using the Wilcoxon signed ranks test with the help of SPSS obtained a significance level of a = 0.05 and the results were p = 0.000 which means p <0.05, namely H0 is rejected and H1 is accepted, which means that there is an effect of health education with audiovisual methods on aid knowledge. The first is burns to housewives in General Poly Room PKM Puri Mojokerto Regency. Keywords: Health Education, Audiovisual, Burns, Knowledge Level